Technical Analysis and Efficient Market Hypothesis in the Nepal Stock Exchange (NEPSE) - Lamichhane, Bhubaneshwar (Academia Research Journal, 2023)
Stock exchange is a trading platform for the buyer and seller of securities. The stock exchange acts as a “barometer” of the health of the economy or considered a mirror of economy. If the market as a whole expects economic prospects to improve, share price will rise, and vice versa. The history of securities market began in Nepal with the flotation of shares by Biratnagar Jute Mills Ltd and Nepal Bank Ltd in 1937 A.D. Introduction of the company Act in 1964 A.D., and the establishment of Securities Exchange Center Ltd in 1976 was other significant developments relating to capital markets in Nepal. At present there is only one stock exchange in Nepal, which is also called secondary market i.e. Nepal Stock Exchange (NEPSE). Nowadays, Nepal’s stock market has become major area of investments. Basically, there are two approaches of analyzing the securities: fundamental analysis and technical analysis. Beside these there is another technique for analyzing the share price behavior that is called efficient market hypothesis. Each price of an individual share is independent of the previous price. The price of a moment does not affect the price of another moment. This type of moment of prices is called random walk of prices.